The Effectiveness of Hypnoteaching Method toward Students Speaking Anxiety - Salma Aida Maftuhah; Fitri Hilmiyati; Selnistia Hidayani (English Education, Linguistics, and Literature Journal, 2023)
The purpose of this study was to measure the effectiveness of hypnoteaching method reducing speaking anxiety in eleventh graders at SMA Al-Asmaniyah. The research question of this study is “How is the effectiveness of hypnoteaching method in reducing students' speaking anxiety for eleventh graders in middle school Al-Asmaniyah and the purpose of this study was "To measure the effectiveness of hypnoteaching method in reducing students' speaking anxiety ". Researchers used Pre-Experimental method and involved one class, as research the experimental class. In the experimental class, the researcher applied the hypnoteaching method. The population in this study were students of class X SMA Al-Asmaniyah, participant sample 62 students. The sample of this research was taken using purposive sampling technique, which only took 20 of X IPS as the experimental class. To obtain data, researcher distributed questionnaires and interviews. Questionnaires were distributed before and after treatment. Questionnaires were used to obtain data about psychological research. Researchers used a Likert Scale to measure the results of the questionnaire. The questionnaire used by the researcher was adopted from by Horwitz at al (1986). The use of hypnoteaching in this study can reduce students' speaking anxiety. The mean score of the questionnaire before and after treatment was different. The mean score before treatment was 94.25 and the mean score after treatment was 51.45. This shows that there is a decrease in students' speaking anxiety. This can be seen from the students' answers in the questionnaire. There are 60% students with low anxiety levels, 35% students with moderate anxiety levels, and 5% students with high anxiety levels.The results showed that there were differences in scores between the pre and post questionnaires. The pre-questionnaire score was higher than after the questionnaire. The higher the score, the higher the anxiety level and the lower the score, the lower the anxiety level. This study succeeded in reducing students' anxiety in speaking, but students' anxiety was still high.